Pengaruh Citra Merek Dan Iklan Terhadap Keputusan Pembelian Produk Hand And Body Lotion Marina - Soedargo, Bayu; Mulya, Siti Zulfah Halimatu; Riwoe, Febry Lodwyk Rihe (Jurnal Aplikasi Bisnis Kesatuan, 2023)
The buying decision-making process will be influenced by brands and advertising. The term "brand image" relates to how people view a specific brand, whereas "advertising factors" refers to marketing methods used to sell items. The goal of this study is to determine whether Marina Hand and Body Lotion purchase decisions are influenced by brand perception, whether those decisions are also influenced by advertising, and whether those decisions are influenced by both brand perception and advertising jointly, particularly for Gen Z consumers who live in the city of Bogor. 130 respondents were chosen using a purposive selection technique, and the Hair et al. formula was applied. Respondents' responses provided the information needed. The Statistical Package for the Social Sciences (SPSS), which employs the Multiple Linear Regression Analysis approach, was used to process the 130 respondents' survey responses. The study discovered that: (1) Brand image significantly and favorably influenced customers' decisions to buy Marina hand and body lotion; (2) Advertising significantly and favorably influenced customers' decisions to buy Marina hand and body lotion; and (3) Overall, Marina's brand image and advertising significantly and favorably influenced customers' decisions to buy Marina hand and body lotion.                                  Keywords : Brand Image, Advertising, Purchase Decisions and Consumers